Evaluation the best condition of Fibrinolytic protease production using factorial design by Streptomyces sp DPUA 1573 - Silva, J. M. (2012)
XI Reunião Regional Nordeste da SBBq | 4th International Symposium in Biochemistry of Macromolecules and Biotechnology